2006
DOI: 10.1300/j030v15n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-Life of Tail Meat of the Giant River Prawn,Macrobrachium rosenbergii, Stored on Ice

Abstract: The objective of this study was to evaluate the shelf-life of peeled giant river prawn Macrobrachium rosenbergii stored directly in contact with ice (DCI), and without direct contact with ice (WCI). The prawns from DCI treatment showed an intense leaching of non-protein nitrogen (NPN) and total volatile bases nitrogen (TVB-N), thus suggesting that NPN or TVB-N should not be used as freshness indicators of peeled tails stored directly in contact with ice. Loss of flavor and a quick texture tactile decrease with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
4
7
0
1
Order By: Relevance
“…Freshwater prawn contained high moisture and protein with respective values from 77.51 ± 0.48% to 78.37 ± 0.02% and from 19.56 ± 0.26% to 19.91 ± 0.42%, and a very low level of lipid and ash, around 0.2% and 1%, respectively. These proximate compositions are very close to the values of freshwater prawn reported by Gaberz Kirschnik, Viegas, Valenti, and Oliveira (), with moisture, protein, lipid, and ash being 78.25%, 18.59%, 0.29%, and 1.35%, respectively. Guevara, Nan, and Shiau () found that white shrimp had 71.1 to 78.9% moisture, 18.6 to 23.2% protein, 0.23 to 0.71% lipid, and 1.39 to 2.92% ash.…”
Section: Resultssupporting
confidence: 89%
“…Freshwater prawn contained high moisture and protein with respective values from 77.51 ± 0.48% to 78.37 ± 0.02% and from 19.56 ± 0.26% to 19.91 ± 0.42%, and a very low level of lipid and ash, around 0.2% and 1%, respectively. These proximate compositions are very close to the values of freshwater prawn reported by Gaberz Kirschnik, Viegas, Valenti, and Oliveira (), with moisture, protein, lipid, and ash being 78.25%, 18.59%, 0.29%, and 1.35%, respectively. Guevara, Nan, and Shiau () found that white shrimp had 71.1 to 78.9% moisture, 18.6 to 23.2% protein, 0.23 to 0.71% lipid, and 1.39 to 2.92% ash.…”
Section: Resultssupporting
confidence: 89%
“…0.60±0.03%, the slight decrease (0.31±0.01%) in fat content might be attributed to increase in moisture content of Acetes. Similar results were observed by Kirshnick et al, 2006. Similarly ash content was reduced from 2.24±0.02% to 2.02±0.07%. However, the decrease in ash content was negligible.…”
Section: Changes In Proximate Compositionsupporting
confidence: 89%
“…This gradual increase may be attributed to the long adoption period for pscychrotrophs during ice storage. Kirshnick et al, (2006) also reported a gradual increase of bacterial count in ice stored M. rosenbergii. Zeng et al, (2005) reported that total viable counts of shrimp (P. borealis) increased during different ice stored conditions.…”
Section: Microbial Changesmentioning
confidence: 82%
See 1 more Smart Citation
“…In freezer, the storage was extended up to 75 days, the significant moisture losses in later storage periods was due to the myofibrillar distortion resulting in the poor water detention ability of the meat. According to Kirschnik et al (2006), moisture content was constant for 14 days in samples of tail meat of the giant river prawn, (Macrobrachium rosenbergii) stored without direct contact in ice, while in samples stored in direct contact with ice it increased approximately 6%, revealing absorption of water through exposed surface of meat and decrease in solid content (crude protein) during early stages of storage in ice.…”
Section: 3mentioning
confidence: 99%